BERITA KRIMINAL DAN PERHATIAN ORANG TUA - Syafruddin Ritonga (PERSPEKTIF, 2013)
This research is a mass communication entitled "NEWS OF CRIMINAL AND ATTENTION PARENTS (Crime News Presentation Effects in Pos Metro Metro Parents Against Attention in Children in the village of Bandar Sei Tuan Klippa Kecataman Percut Deli Serdang)â€. The problem in this study is whether the effect of the presentation of crime news in Medan Post Metro Parents Against Attention in Children in the Village District Klippa Percut Bandar Sei Tuan Kabupaten Deli Serdang. The purpose of this study is how the presentation of crime news in Medan Post Metro Parents Against Attention in Children in the Village District Klippa Percut Bandar Sei Tuan Kabupaten Deli Serdang. This research was conducted with the population of 12 neighborhood take 6 environment with the proposed population is 835 people.